Propaganda wars : how the global elite control what you see, think, and feel - Beck, Glenn; Haskins, Justin (Director of the Stopping Socialism Center) (Forefront Books/Mercury Ink, 2024)
Authors Glenn Beck and Justin Hoskins break down propaganda campaigns by global and corporate elites.